Development and initial validation of international severity scoring system for familial Mediterranean fever (ISSF). Issue 6 (28th January 2016) - Demirkaya, Erkan; Acikel, Cengizhan; Hashkes, Philip; Gattorno, Marco; Gul, Ahmet; Ozdogan, Huri; Turker, Turker; Karadag, Omer; Livneh, Avi; Ben-Chetrit, Eldad; Ozen, Seza; ,
Abstract : Objective: To develop widely accepted international severity score for children and adult patients with familial Mediterranean fever (FMF) that can be easily applied, in research and clinical practice. Methods: Candidate severity criteria were suggested by several FMF expert physicians. After three rounds of Delphi survey, the candidate criteria, defined by the survey, were discussed by experts in a consensus meeting. Each expert brought data of clinical manifestations, laboratory findings and physician's global assessments (PGAs) of minimum 20 patients from their centres. We used the PGAs for disease severity as a gold standard. Logistic regression analysis was used to evaluate the predicting value of each item, and receiver operating characteristic curve analysis was performed to demonstrate the success of the criteria set. Results: A total of 281 patients consist of 162 children and 119 adults with FMF were enrolled and available for validity analysis: Nine domains were included in the final core set of variables for the evaluation of disease severity in FMF. The International Severity Score for FMF (ISSF) may reach a maximum of 10 if all items are maximally scored. The threshold values to determine: severe disease ≥6, intermediate disease 3–5, mild disease ≤2. Area under the curve was calculated as 0.825 for this set in the whole group. Conclusions: The initial validity of ISSF both in children and adult with FMF was demonstrated. We anticipate that it will provide a robust tool to objectively define disease severity for clinical trials, future research as well as for therapeutic decisions in managing patients with FMF.